Successful treatment with steroid and cyclosporine A in a patient with immunoglobulin A–proliferative glomerulonephritis with monoclonal immunoglobulin deposits. Issue 8 (29th July 2018) - Sato, Keisuke; Makabe, Shiho; Iwabuchi, Yuko; Kojima, Kaori; Sato, Masayo; Kataoka, Hiroshi; Moriyama, Takahito; Taneda, Sekiko; Tsuchiya, Ken; Nitta, Kosaku; Mochizuki, Toshio
Abstract: We report a case of glomerulonephritis with monoclonal immunoglobulin (Ig) A deposits as a form of monoclonal gammopathy of renal significance (MGRS) caused by monoclonal immunoglobulins without blood disorders in a 41‐year‐old woman. She developed lower leg oedema and was hospitalized because of nephrotic syndrome. Serum and urine were negative for M protein, and the free light chain κ/λ ratio was within the normal range. Renal histopathological findings included mesangial proliferation, endocapillary cell proliferation, and a double‐contour appearance of the capillary walls. Immunofluorescent staining indicated IgA and C3 deposits on the mesangium and capillary walls. Only λ chain and IgA1 deposits were noted. Fine granular sub‐endothelial deposits with no specific structure were observed under electron microscopy. The patient was diagnosed with IgA–proliferative glomerulonephritis with monoclonal immunoglobulin deposits (IgA‐PGNMID). The patient had decreased urine protein and sediment erythrocytes after she underwent two rounds of steroid pulse therapy and oral steroid therapy, but proteinuria and haematuria still remained. Four months later, the patient was administered 50 mg/day cyclosporine (CsA), and proteinuria and haematuria dramatically decreased. Only a few case reports have been published on IgA‐PGNMID. This case is rare in that the patient achieved successful treatment using a combination of steroids and CsA.